Experience and the Space of Reasons Rorty and McDowell on Kant and Wittgenstein - آزادپور, محمد (جاویدان خرد, 2022)
John McDowell and Richard Rorty draw on Kant’s influential account of experience. For Rorty, Kant is the antagonist who succumbs to foundationalism or what Sellars calls the Myth of the Given and Wittgenstein is the hero who helps in overcoming the siren call of the Myth. McDowell, however, is ambivalent toward Kant. With Sellars, he applauds Kant as the hero who helped us vanquish the Myth of the Given. But he argues that Kant failed to recognize the full strength of his account of experience and capitulated to a subjective idealism. Wittgenstein, for McDowell, is the hero who helps us achieve an account of experience that gets to the things themselves. I adjudicate the philosophical and the exegetical tensions between Rorty and McDowell and support the latter’s approach to experience and to the reading of Kant and Wittgenstein.